A CORRELATIONAL STUDY ON ACADEMIC STRESS AND SELF - EESTEEM AMONG HIGHER SECONDARY STUDENTS IN SELECTED SCHOOLS OF UDUPI DISTRICT - S., Nikitha; Jose, Tessy Treesa; Valsaraj, Blessy Prabha (Journal of Health and Allied Sciences NU, 2014)
This study identified the academic stress and self - esteem among higher secondary school students in selected private schools of Udupi district. It also found out the existing correlation between academic stress and self-esteem. Academic stress rating scale, constructed by the researcher and Rosenberg self-esteem scale were used for the data collection. Questionnaires were completed by 96 first year higher secondary students of science batch. Academic stress rating scale was a four point scale which includes 32 statements regarding examination stress, stress from peers, intrapersonal stress, study habit and time management. The study found that 80.20% students have moderate stress, 13.5% have mild stress and 6.2% have severe stress. Among the subjects 82.30% were having normal self - esteem and 6.2% were having low self- esteem. Significant but low negative relationship is found between academic stress and self-esteem.
Keywords: academic stress; self-esteem; higher secondary school students